Enter the values for the highlighted variables to complete the steps to the sum (3x)/(2x - 6) + 9/(6 - 2x) = (3x)/(2x - 6) + 9/(a(2x - 6)) = 3x 2x-6 + 6 2x-6 = 3x-c 2x-6 = d(x-x) f(x-3) =g

Respuesta :

Answer:

a= -1

b= -9

c=9

d=3

e=3

f=2

[tex]g=\frac32[/tex]

Step-by-step explanation:

Rule of sign:

  1. (-)×(+)=(-), (-)÷(+)=(-)
  2. (+)×(-)=(-) , (+)÷(-)=(-)
  3. (+)×(+)=(+), (+)÷(+)=+
  4. (-)×(-)=(+), (-)÷(-)=(+)

Given that,

[tex]\frac{3x}{2x-6}+\frac{9}{6-2x}[/tex]

We can rewrite 6-2x as 2x-6, taking (-1) as common factor of (6-2x)

[tex]=\frac{3x}{(2x-6)}+\frac{9}{-1(2x-6)}[/tex]

So, a= -1

[tex]\frac9{-1}=-9[/tex]

[tex]=\frac{3x}{(2x-6)}+\frac{-9}{(2x-6)}[/tex]

So, b= -9

The L.C.M of (2x-6) and (2x-6) is (2x-6)

and (2x-6)÷(2x-6)=1

[tex]=\frac{1 \times 3x+1\times (-9)}{(2x-6)}[/tex]

[tex]=\frac{( 3x-9)}{(2x-6)}[/tex]

∴c= 9

(3x-9) has a common factor 3 and (2x-6) has a common factor 2.

(3x-9)=3(x-3)

(2x-6)=2(x-3)

[tex]=\frac{3(x-3)}{2(x-3)}[/tex]

∴d=3, e=3 and f=2

Since the denominator and numerator are the product of two polynomial. So, if there is any common element, then can cancel the common factor.

Here the common factor is (x-3). So cancel  out (x-3).

[tex]=\frac32[/tex]

[tex]\therefore g=\frac32[/tex]

Answer:

A= -1

B=-9

C=9

D=3

E=3

F=2

G=1.5

On edge

Step-by-step explanation: